Energy loss and cooling of relativistic highly charged uranium ions interacting with an internal hydrogen droplet target beam - Petridis, Nikolaos; Kalinin, A.; Popp, U.; Gostishchev, V.; Litvinov, Yu. A.; Dimopoulou, C.; Nolden, F.; Steck, M.; Kozhuharov, C.; Thorn, D. B.; Gumberidze, A.; Trotsenko, S.; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2011)
We present measurements of the energy loss of relativistic highly charged uranium ions interacting with a target beam of near-liquid density hydrogen droplets at the experimental storage ring (ESR) at GSI. Our results reveal that a liquid droplet target beam virtually behaves like a homogeneous gas jet target with respect to both energy loss and ion beam cooling. We also provide first results on ion beam cooling efficiency at high hydrogen area target densities, which are consistent with numerical estimations based on a simple model of the cooling force.
Gesehen am 30.11.2022